Night rounds in the menagerie sleepycast - Wurfel, Marlene (My University, 2018)
This Tales from the Lilypad original sleepycast is to help listeners get sleepy at sleepytime. Go with Jack, the Great Pyrenees dog, as he makes his night rounds of the castle menagerie while the prince and princess sleep. All is well, but Jack keeps watch anyway. He's a guard-dog, so it's his job to check on all those sleeping animals.
Keywords: storytelling; children's stories